Hakikat Sui Generis Keilmuan Ilmu Hukum Dalam Aliran Filsafat (The Pure Theory Of Law) Oleh Hans Kelsen - Aqrabin Faqih, Ghazwan (Cv. Kalimasada Group, 2024)
The study aims to discuss the Sui Generis Nature of Legal Science in the school of philosophy The Pure Theory of Law by Hans Kelsen. This study is a normative legal study with a conceptual approach that is analyzed using a descriptive qualitative method. In relation to the Sui Generis Principle of Legal Science, which means that legal science has its own characteristics that distinguish it from other sciences, legal science cannot be classified and included in the humanities or social sciences because its nature stands alone, meaning that this sui generis principle is very firm in wanting to maintain the nature (epistemology) of legal science from aspects outside the law. If analyzed, this has similarities in the pure legal philosophy of Hans Kelsen in his teachings The Pure Theory of Law which is very firm in wanting to separate legal science from foreign elements, be it politics, social, economics and ethics. Because Legal Science is a science that has a normative scientific character.